Development and Validation of Most Essential Learning Competency-Based Workbook in General Physics 1 for Senior High School - Araza, Fatima; Magnaye, Louiesito Jr. (SEAQIS Journal of Science Education, 2023)
One of the best things a teacher can do to help students achieve a quality learning process is to create and validate learning resources or instructional materials, such as a workbook. With this, a descriptive-developmental research design was utilized in development and validation of most essential learning competency-based workbook in General Physics 1 for Senior High School. The development of the MELC-based workbook in General Physics 1 was based on the 85 most essential learning competencies for the whole semester using the six components namely topics, specific objectives, key concepts, directions, activities and reflection. The developed workbook was fielded to the three groups of respondents such as group of experts, teachers handling General Physics 1 and grade 12 STEM students. The study disclosed that these groups of respondents evaluated the workbook to be both content and face valid as evidenced in their assessment labeled as “agree” in the indicators. Moreover, the results showed that the MELC-based workbook has met the standard and can be used as a learning material in teaching General Physics 1 for Senior High School. As such, it was recommended by the researchers that the said workbook be used as learning material in teaching General Physics 1 for Senior High School. Further study on the effectiveness of the said workbook must be warranted with consideration to some factors.